Antibodies to interleukin 12 abrogate established experimental colitis in mice (The Rockefeller University Press, 1995)
In this study, we describe a novel murine model of chronic intestinal inflammation induced by the hapten reagent 2,4,6-trinitrobenzene sulfonic acid (TNBS). Rectal application of low doses of TNBS in BALB/c and SJL/J mice resulted in a chronic transmural colitis with severe diarrhea, weight loss, and rectal prolapse, an illness that mimics some characteristics of Crohn's disease in humans. The colon of TNBS-treated mice on day 7 was marked by infiltration of CD4+ T cells; furthermore, in situ polymerase chain reaction studies revealed high levels of interferon (IFN)-gamma mRNA in diseased colons. Isolated lamina propria (LP) CD4+ T cells from TNBS-treated mice stimulated with anti-CD3 and anti-CD28 antibodies exhibited a Th1 pattern of cytokine secretion: a 20-50-fold increase in IL-2 and IFN-gamma levels and a 5-fold decrease in IL-4 levels as compared with those of stimulated LP CD4+ T cells from control BALB/c mice. Administration of monoclonal anti-IL-12 antibodies to the TNBS-treated mice both early (at 5 d) and late (at 20 d) after induction of colitis led to a striking improvement in both the clinical and histopathological aspects of the disease and frequently abrogated the established colitis completely. Furthermore, LP CD4+ T cells isolated from anti-IL-12-treated mice failed to secrete IFN-gamma upon in vitro stimulation. In summary, the data demonstrate the pivotal role of IL-12 and IFN-gamma in a TNBS-induced murine model of chronic intestinal inflammation. Furthermore, they suggest the potential utility of anti-IL-12 antibodies in patients with Crohn's disease.